2008
DOI: 10.1159/000156489
|View full text |Cite
|
Sign up to set email alerts
|

The Anaesthetic Steroid Alphaxalone Positively Modulates α<sub>1</sub>-Glycine Receptor Function

Abstract: Inhibitory synaptic transmission within the dorsal horn of the spinal cord plays a key role in the processing of nociceptive signals, and mainly involves glycine. We have studied the effects of alphaxalone on α1 homomeric glycine receptors expressed in a mammalian expression system (HEK 293 cells) using the whole-cell patch-clamp technique. Our experiments showed a coactivating effect of alphaxalone with a concentration for half-maximum activation (EC50) of the effect of a low glycine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The effect of neurosteroids on the GABA A receptor channel is well established (Harrison and Simmonds, 1984). There are also reports of allosteric actions of neurosteroids on nicotinic ␣4␤2, N-methyl-D-aspartate, and glycine receptors (Paradiso et al, 2001;Ahrens et al, 2008;Johansson et al, 2008). Sex and adrenal steroid hormones influence P2XR expression by activating cytosolic receptors, leading to changes in transcriptional regulation Fan et al, 2009;Urabe et al, 2009).…”
Section: G Multiple Roles Of Steroid Hormones On P2x Receptor Functionmentioning
confidence: 99%
“…The effect of neurosteroids on the GABA A receptor channel is well established (Harrison and Simmonds, 1984). There are also reports of allosteric actions of neurosteroids on nicotinic ␣4␤2, N-methyl-D-aspartate, and glycine receptors (Paradiso et al, 2001;Ahrens et al, 2008;Johansson et al, 2008). Sex and adrenal steroid hormones influence P2XR expression by activating cytosolic receptors, leading to changes in transcriptional regulation Fan et al, 2009;Urabe et al, 2009).…”
Section: G Multiple Roles Of Steroid Hormones On P2x Receptor Functionmentioning
confidence: 99%
“…However, previous studies have shown that the ability of alfaxalone to potentiate GlyR activity was minimal and the concentration of alfaxalone necessary to potentiate α 1 GlyR in HEK 293 cells was outside the clinically relevant dose ranges (Ahrens et al, 2008). By contrast, the inhibition of α 1 glycinergic transmission causes exaggerated startle responses, as seen with hyperekplexia and strychnine poisoning (Zhou et al, 2002) and we hypothesised alfaxalone might produce similar suppressive effects on glycinergic transmission.…”
Section: Premedication Agents Reduced the Incidence And Severity Of Tmentioning
confidence: 75%
“…The potentiation of α1 GlyRs was much less pronounced for alfaxalone than that of ORG20599 and minaxolone, suggesting that GlyR modulation does not play a critical role for the anaesthetic action of neurosteroids (Weir et al, 2004). Similarly, the concentration of alfaxalone necessary to potentiate the α1 GlyR subunits, transiently transfected into transformed human embryonic kidney (HEK 293) cells, was much higher than that required for GABA A R modulation, suggesting that GlyR potentiation by neurosteroids would fall outside a clinically relevant range (Ahrens et al, 2008).…”
Section: Neurosteroids and Their Neuronal Actionsmentioning
confidence: 99%
See 2 more Smart Citations